DYNAMICS OF PHYSICAL DEVELOPMENT AND FUNCTIONAL READINESS OF PRE-SCHOOL CHILDREN - M.N. Kuznetsova; S.D. Polyakov; I.T. Korneeva; L.V. v; A.D. Khristochevskiy; S.V. Khrushchev ("Paediatrician" Publishers LLC, 2010)
The article presents the analysis of a dynamics of physical development and functional readiness of children 3-7 years old, studying in children's educational institution with daily stay. Authors revealed statistically significant (р < 0,001) correlation connections between the age and the rates of functional readiness (except flexibility; р = 0,08). Sanitary and pedagogical measures, performed in children's educational institution, favor to physical development of pre-school children and locomotive experiences and skills. Key words: pre-school children, health, physical development, functional readiness. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):12-16)